Deep-sea high-rate high-safety lithium ion battery composite diaphragm and preparation method thereof

By using modified nanoconductive agents in lithium-ion battery separators, the problem of insufficient high-rate discharge performance and safety of existing separators in deep-sea high-voltage environments is solved, and higher wetting, tensile strength and Li+ conductivity are achieved The growth of lithium dendrites is avoided and the safety and magnification capacity of the battery is improved.

CN119401054AActive Publication Date: 2025-02-07WUHAN INSTITUTE OF MARINE ELECTRIC PROPULSION (THE 712TH RESEARCH INSTITUTE OF CHINA STATE SHIPBUILDING CORP LTD)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411381182.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators cannot meet the requirements of high-rate discharge and safety in deep-sea high-voltage environments, mainly due to poor thermal stability, which leads to local heat accumulation and the growth of lithium dendrites.

Method used

By adding sodium p-toluene sulfinate and pyrrole to the nanoconductive agent dispersion, a polymer containing N-H functional group and a nitrogen heterocyclic ring structure is formed, coated on the surface of the nanoconductive agent to form a modified nanoconductive agent, and sprayed Cover the surface of the diaphragm substrate to enhance the performance of the diaphragm.

Benefits of technology

Modified nanoconductive agent improves the wetting and tensile strength of the separator, reduces the interface resistance, enhances Li+ conductivity, avoids local heat accumulation and the growth of lithium dendrites, and improves the safety and magnification capacity of the battery. It meets the high-rate discharge requirements in deep-sea high-voltage environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119401054A_ABST
    Figure CN119401054A_ABST
Patent Text Reader

Abstract

The invention relates to a deep-sea high-rate high-safety lithium ion battery composite diaphragm and a preparation method thereof.The preparation method comprises the following steps that sodium p-toluenesulfinate and pyrrole are added into nanometer conductive agent dispersion liquid and stirred to be uniform, and mixed liquid A is obtained; under the conditions of ice-water bath and stirring, dropwise adding a (NH4) 2S2O8 solution into the mixed solution A to obtain a mixed solution B; and carrying out solid-liquid separation, washing and drying on the mixed solution B to obtain the modified nano conductive agent. And S4, uniformly spraying the modified nano conductive agent on the surface of the diaphragm substrate to obtain the lithium ion battery composite diaphragm. Sodium p-toluenesulfinate and pyrrole form a polymer containing an N-H functional group and a nitrogen heterocyclic ring structure under the action of (NH4) 2S2O8, the polymer coats the surface of the nano conductive agent, so that the modified nano conductive agent with an inorganic-organic core-shell structure is obtained, and the composite diaphragm obtained by compounding the modified nano conductive agent with a diaphragm matrix has good wettability and high tensile strength and can be applied to the field of lithium ion batteries. And the rate capacity is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery separators, and in particular to a deep-sea large-rate high-safety lithium-ion battery composite separator and a preparation method thereof. Background Art

[0002] As the core component of lithium batteries, the performance of the separator is directly related to the electrochemical performance and safety of lithium batteries. The common separators based on meta-aramid (PMIA), cellulose, polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylonitrile (PAN) and polyethylene terephthalate (PET) on the market have different advantages and disadvantages and can be applied to lithium-ion batteries in different use environments under normal pressure.

[0003] However, in the field of manned / unmanned submersibles at 10,000 meters in the deep sea, the pressure is 100MPa or even higher, and a high-rate discharge is required. In view of the requirements of high-rate discharge in deep-sea environments, the electrolyte membrane must meet the requirements of wettability, thermal stability, pressure shrinkage resistance, high ionic conductivity, mechanical properties, chemical stability, and no reaction with electrode materials and electrolytes.

[0004] Among them, electrochemical performance and safety are the most critical factors in the deep-sea high-rate discharge environment. Conventional diaphragms cannot meet the requirements of withstand voltage and high-rate discharge at the same time. This is mainly because the high-rate discharge process under high pressure will produce local heat accumulation, thereby accelerating the Li + The local reaction rate decreases, forming lithium dendrites. Due to its poor thermal stability, commercial polyolefin separators cannot solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, provide a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm and a preparation method, and solve the technical problem that the diaphragm in the prior art has poor high-rate discharge performance under a pressure-resistant environment.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm, comprising the following steps: S1, adding sodium p-toluenesulfinate and pyrrole to the nano-conductive agent dispersion, and stirring to obtain a mixed solution A; S2, adding (NH4)2S2O8 solution dropwise to the mixed solution A under ice-water bath and stirring conditions to obtain a mixed solution B; S3, the mixed solution B is subjected to solid-liquid separation, washing and drying to obtain a modified nano-conductive agent; S4, spraying the modified nano-conductive agent uniformly on the surface of the diaphragm substrate to obtain a lithium-ion battery composite diaphragm.

[0007] In a second aspect, the present invention provides a lithium-ion battery composite separator prepared by the above preparation method.

[0008] Compared with the prior art, the beneficial effects of the present invention include: The present invention uses sodium p-toluenesulfinate and pyrrole as raw materials. Under the action of (NH4)2S2O8, sodium p-toluenesulfinate and pyrrole can form a high molecular polymer containing NH functional groups and nitrogen-containing heterocyclic structures. The NH functional group has adhesion, and the prepared polymer can be coated on the surface of the nano conductive agent, thereby obtaining a modified nano conductive agent with an inorganic-organic core-shell structure; the modified nano conductive agent is composited with a diaphragm matrix, and the modified nano conductive agent strengthens the diaphragm matrix. At the same time, the core-shell structure of the modified nano conductive agent avoids the short circuit risk caused by the conductivity of the internal conductive agent, and retains the hydrophilicity of the surface of the external polymer containing multiple NH groups. Therefore, the composite diaphragm obtained by the present invention has good wettability and high tensile strength, which promotes low interface resistance and high Li + The electrical conductivity helps to obtain excellent rate capacity and high safety. The composite diaphragm of the present invention disperses local heat sources and avoids the violent growth of lithium dendrites caused by local heat accumulation, thereby effectively improving the safety of lithium-ion batteries and meeting the application requirements of high deep-sea pressure and high rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 It is a battery cycle curve diagram of a conventional PP-based diaphragm and a composite diaphragm obtained in the present invention at 100 MPa; Figure 2 It is the pressure resistance test result of the composite diaphragm of the present invention. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] The present invention provides a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm and a preparation method thereof, and improves the high-rate discharge performance of the diaphragm under a pressure-resistant environment through a modification method. Specifically, by modifying the lithium-ion battery diaphragm, high lithium ion conductivity and lithium ion transfer number are achieved, lithium dendrite growth is effectively reduced, and the high-rate discharge process of the lithium-ion battery at 100MPa is achieved to be safe and stable.

[0012] In a first aspect, the present invention provides a method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm, comprising the following steps: S1, adding sodium p-toluenesulfinate and pyrrole to the nano-conductive agent dispersion, and stirring to obtain a mixed solution A; S2, adding (NH4)2S2O8 solution dropwise to the mixed solution A under ice-water bath and stirring conditions to obtain a mixed solution B; S3, the mixed solution B is subjected to solid-liquid separation, washing and drying to obtain a modified nano-conductive agent; S4, spraying the modified nano-conductive agent uniformly on the surface of the diaphragm substrate to obtain a lithium-ion battery composite diaphragm.

[0013] Preferably, in step S1, the nano-conductive agent comprises nitrogen-doped carbon nanotubes (NCNTs), which are products that can be purchased conventionally on the market, and the nitrogen doping amount is 10 to 30 at %.

[0014] Preferably, in step S1, the concentration of the nano-conductive agent dispersion is 0.6-1.6 mg / mL.

[0015] Further preferably, the specific preparation steps of the nano-conductive agent dispersion include: adding the nano-conductive agent to deionized water, firstly performing ultrasonic treatment for 1.5 to 2.5 hours; then stirring at a speed of 800 to 1000 rpm for 30 to 40 minutes under 0 to 3°C water bath conditions to obtain the nano-conductive agent dispersion.

[0016] Preferably, in step S1, the mass ratio of the nano-conductive agent to sodium p-toluenesulfinate is 1:(5-7); the ratio of the nano-conductive agent to pyrrole is (60-80) mg:(60-80) μL.

[0017] Preferably, the ratio of the nano-conductive agent in step S1 to the (NH4)2S2O8 in step S2 is (60-80) mg: (1-1.2) mmol.

[0018] Further preferably, in step S2, the concentration of the (NH4)2S2O8 solution is 0.1 mol / L, and the ratio of the nano-conductive agent to the (NH4)2S2O8 solution is (60-80) mg: (10-12) mL.

[0019] Preferably, in step S2, stirring is performed for 3.5 to 4.5 hours. The present invention controls the polymerization reaction by stirring time to avoid polymerization failure and failure to obtain the target polymer.

[0020] Preferably, in step S3, washing is performed by washing with deionized water for 3 to 5 times; and drying is performed by vacuum drying at 60 to 70° C. for 10 to 14 hours.

[0021] Preferably, in step S4, the spraying is performed by electrostatic spraying; the spraying amount of the modified nano conductive agent is 2-10 mg / cm 2 ; The diaphragm matrix adopts PP diaphragm.

[0022] In a second aspect, the present invention provides a lithium-ion battery composite separator prepared by the above preparation method.

[0023] The main mechanism of action and advantages of the present invention are: The present invention uses sodium p-toluenesulfinate and pyrrole as raw materials, and initiates the polymerization of monomer pyrrole into polypyrrole under the oxidation of (NH4)2S2O8. Sodium p-toluenesulfinate is used as a dopant in the polymer, and by controlling the raw material ratio and temperature, a high molecular polymer containing NH functional groups and nitrogen-containing heterocyclic structures can be formed. The NH functional group has adhesion, and the prepared polymer can be coated on the surface of the nano-conductive agent to form an inorganic-organic structure with a core-shell structure, thereby obtaining a modified nano-conductive agent. The core-shell structure of the modified nano-conductive agent avoids the short circuit risk caused by the conductivity of the internal conductive agent, and retains the hydrophilicity of the external polymer surface containing multiple NH groups; after the modified nano-conductive agent is sprayed on the surface of the diaphragm substrate, it can effectively play a reinforcing role. Therefore, the composite diaphragm obtained by the present invention has good wettability and high tensile strength, which promotes low interface resistance and high Li + The electrical conductivity further contributes to obtaining excellent rate capacity and high safety. The composite diaphragm of the present invention disperses local heat sources, avoiding the violent growth of lithium dendrites caused by local heat accumulation, thereby further improving the safety of LIBs and meeting the application requirements of high deep-sea pressure and high rate.

[0024] The present invention is further described in detail below through specific examples. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially. The nitrogen doping amount of the nano-conductive agent NCNT is 20at%.

[0025] Example 1 A method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm comprises the following steps: S1, add 70 mg of nano-conductive agent NCNT into 100 mL of deionized water, ultrasonicate for 2 hours, transfer to a low-temperature water bath at 0-3°C, and stir at 1000 rpm for 30 minutes to obtain a nano-conductive agent dispersion; Add 420 mg of sodium toluenesulfinate and 70 μL of pyrrole to the nano-conductive agent dispersion and stir for 30 min to obtain a uniform mixed solution A; S2, in an ice-water bath at 0°C with stirring, add 10 mL of 0.1 M (NH4)2S2O8 solution to the mixed solution A, and stir for 4 hours to obtain a mixed solution B; S3, the mixed solution B is filtered, washed with deionized water for 4 times and vacuum dried in an oven at 65° C. for 12 hours to obtain a modified nano conductive agent; the modified nano conductive agent is formed by coating a high molecular polymer on the nano conductive agent, and the high molecular polymer contains an NH functional group and a nitrogen heterocyclic structure; S4, the modified nano-conductive agent is evenly sprayed on the surface of the diaphragm substrate (PP diaphragm) by electrostatic spraying, and the spraying amount of the modified nano-conductive agent is 5 mg / cm 2 , and obtain a composite diaphragm.

[0026] Comparative Example 1 The diaphragm substrate in Example 1: PP diaphragm is directly used.

[0027] Performance Testing 1. Test the charge and discharge performance of the diaphragm by assembling button batteries. The positive electrode material is lithium iron phosphate, and the negative electrode material is a lithium sheet. They are separated by different types of diaphragms in Example 1 and Comparative Example 1, and 100 microliters of 15wt% commercial lithium hexafluorophosphate electrolyte is added dropwise, and then fixed by button-type positive and negative battery shells to obtain a button-type lithium-ion battery. Then, the charge and discharge performance is tested by the blue power test system, and the discharge rate is 0.5 C. After 50 cycles, the discharge specific capacity of each battery is compared. The results are shown in Table 1. Figure 1 .

[0028] like Figure 1 As shown, the battery assembled with the diaphragm before and after modification, in the initial stage of charge and discharge, the discharge specific capacity of Example 1 is slightly higher than that of Comparative Example 1, and is between 140mAh / g and 150mAh / g. After 50 cycles, the capacity retention rate of Comparative Example 1 is 90.6%, and the capacity retention rate of Example 1 is 95.8%. This shows that the composite diaphragm prepared by using the modified nano-conductive agent has good wettability and liquid retention rate to the electrolyte, so that the battery has a high capacity retention rate and good electrochemical performance. This is attributed to the fact that the modified coating is firmly coated on the surface of the diaphragm, and its particle size is appropriate, the particle size is uniform, and it has good retention of the electrolyte. Therefore, the present invention provides a composite diaphragm for lithium-ion batteries that can be used in the deep sea at 100MPa, with high rate, high safety, three-dimensional conductivity and high wettability.

[0029] 2. Lithium iron phosphate is used as the positive electrode material, spherical graphite is used as the negative electrode material, polylactic acid is used as the binder, dibutyl phthalate is used as the plasticizer, acetylene black is used as the conductive agent, and the electrolyte is used for the deep-sea 10,000-meter battery (Struggler). The diaphragm uses the composite diaphragm obtained in Example 1 to make a 45Ah battery cell.

[0030] The battery is charged at a constant current of 0.2C at normal pressure, with a cut-off voltage of 3.65V. One hour after the charging is completed, a pressure test is performed using a pressure cylinder. When the pressure in the pressure cylinder is increased to 100MPa, a constant current discharge is performed at 20C according to the rated capacity of the battery cell, with a cut-off voltage of 2.5V. One hour after the pressure relief is completed, the battery cell is charged at a constant current of 0.2C at normal pressure, and this cycle is repeated 5 times.

[0031] The results are as follows Figure 2 As shown, the five discharge capacities of the battery cells are 44.279Ah, 44.022Ah, 43.815Ah, 43.703Ah and 43.38Ah, respectively, and the cell capacity retention rates are 100%, 99.42%, 98.95%, 98.70% and 97.97% respectively, and the cell discharge capacity decay is not large. The test results show that the pressure discharge performance of the battery cells of the present invention is not significantly affected by the full sea depth pressure conditions, and all materials meet the requirements of the deep sea of ​​10,000 meters.

[0032] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm, characterized in that: The following steps are involved: S1, adding sodium p-toluenesulfinate and pyrrole to the nano-conductive agent dispersion, and stirring to obtain a mixed solution A; S2, adding (NH4)2S2O8 solution dropwise to the mixed solution A under ice-water bath and stirring conditions to obtain a mixed solution B; S3, the mixed solution B is subjected to solid-liquid separation, washing and drying to obtain a modified nano-conductive agent; S4, spraying the modified nano-conductive agent uniformly on the surface of the diaphragm substrate to obtain a lithium-ion battery composite diaphragm.

2. The method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm according to claim 1, characterized in that: In step S1, the nano-conductive agent includes nitrogen-doped carbon nanotubes.

3. The method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm according to claim 1, characterized in that: In step S1, the concentration of the nano-conductive agent dispersion is 0.6-1.6 mg / mL.

4. The method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm according to claim 1, characterized in that: The specific preparation steps of the nano-conductive agent dispersion include: adding the nano-conductive agent to deionized water, firstly ultrasonically treating it for 1.5 to 2.5 hours; then stirring it at a speed of 800 to 1000 rpm for 30 to 40 minutes in a water bath at 0 to 3°C to obtain the nano-conductive agent dispersion.

5. The method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm according to claim 1, characterized in that: In step S1, the mass ratio of the nano-conductive agent to sodium p-toluenesulfinate is 1:(5-7); the ratio of the nano-conductive agent to pyrrole is (60-80) mg:(60-80) μL.

6. The method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm according to claim 1, characterized in that: The ratio of the nano-conductive agent in step S1 to the (NH4)2S2O8 in step S2 is (60-80) mg: (1-1.2) mmol.

7. The method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm according to claim 6, characterized in that: In step S2, the concentration of the (NH4)2S2O8 solution is 0.1 mol / L, and the ratio of the nano-conductive agent to the (NH4)2S2O8 solution is (60-80) mg: (10-12) mL; Stir for 3.5 to 4.5 hours to obtain mixed solution B.

8. The method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm according to claim 1, characterized in that: In step S3, washing is performed by washing with deionized water for 3 to 5 times; and drying is performed by vacuum drying at 60 to 70° C. for 10 to 14 hours.

9. The method for preparing a deep-sea high-rate and high-safety lithium-ion battery composite diaphragm according to claim 1, characterized in that: In step S4, the spraying is performed by electrostatic spraying; the spraying amount of the modified nano conductive agent is 2-10 mg / cm 2 ; The diaphragm matrix adopts PP diaphragm.

10. A lithium-ion battery composite separator prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of composite diaphragm of lithium-sulphur battery

    CN104393220A

  • Preparation method for modified diaphragm for lithium-sulfur battery, modified diaphragm and lithium-sulfur battery adopting multiple layers of modified diaphragms

    CN105489814A

  • Electrochemical preparation method of alkenyl sulfone compound

    CN108660478A

  • Diaphragm for lithium battery and preparation method of diaphragm

    CN108832057A

  • Lithium ion battery composite diaphragm containing modified inorganic particle and preparation method thereof

    CN111916619A